2022
DOI: 10.3390/biomedicines10061350
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin Inhibits Gastric Cancer Stemness, Modulates Tumor Microenvironment, and Suppresses Tumor Growth through Glucose-Regulated Protein 78 Downregulation

Abstract: Chemotherapy is the treatment of choice for gastric cancer; however, the currently available therapeutic drugs for treatment have limited efficacy. Cancer stemness and the tumor microenvironment may play crucial roles in tumor growth and chemoresistance. Glucose-regulated protein 78 (GRP78) is an endoplasmic reticulum chaperone facilitating protein folding and cell homeostasis during stress and may participate in chemoresistance. Isoliquiritigenin (ISL) is a bioactive flavonoid found in licorice. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The quantification of proteins in exosomes contained in a small quantity of patient serum samples will provide a relatively noninvasive method of diagnosing cancer and its prognosis. In addition, quantification of exosomal proteins, such as GRP78, may be indispensable for elucidating the mechanism of cancer progression, because the scenario of this progression is not yet clarified [ 50 , 51 , 52 ]. We strongly believe that the present technique will provide detailed insight into the tumor microenvironment and cell–cell communication and contribute to elucidating the mechanisms of cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…The quantification of proteins in exosomes contained in a small quantity of patient serum samples will provide a relatively noninvasive method of diagnosing cancer and its prognosis. In addition, quantification of exosomal proteins, such as GRP78, may be indispensable for elucidating the mechanism of cancer progression, because the scenario of this progression is not yet clarified [ 50 , 51 , 52 ]. We strongly believe that the present technique will provide detailed insight into the tumor microenvironment and cell–cell communication and contribute to elucidating the mechanisms of cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…The above results showed that targeting genes with inhibitors or antibodies to inhibit CSCs has potential in treating tumors, which is also applicable in GC. Chien-Hsing Lee et al found that liquiritigenin inhibited the stem cell-like characteristics of GC by down-regulating the expression of glucose-regulated protein 78 and inhibiting the growth of GC [ 54 ]. Therefore, inhibiting GC stemness by inhibiting the expression of GCSCs-related genes is also a method for treating GC.…”
Section: The Role Of Protein-encoding Genes In Gcscsmentioning
confidence: 99%
“…Glucose-regulated protein 78 (GRP78) is involved in various aspects of cancer, such as invasion and metastasis [ 1 ], and GRP78 inhibitors are now considered potential cancer therapy targets [ 2 ]. In the tumor microenvironment, GRP78 contained in exosomes, transport vesicles of about 100-nm in size, is released from cancer cells [ 3 ], where it affects the surrounding cells and induces cancer malignancy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%